Diagnosis of oral lichen planus (Research, Society and Development, 2023)
Oral lichen planus is an autoimmune disease, clinically visible as whitish streaks called Wickham's striae and which, although it has no defined etiology, is associated with some possible causal factors, such as: emotional conditions, use of some dental materials, medications, harmful habits and as a result of trauma. It tends to manifest itself in six different ways: plaque-like (white lesions), papular, ulcerative, atrophic, bullous (red lesions) and reticular, which is the most common and frequent. It is not a rule, but in some cases the appearance of signs and symptoms are common, such as pain, sensation of roughness, alteration in the perception of flavors and skin reactions. Its diagnosis is formed by a set of actions. The objective of this work is to describe the clinical and histological characteristics, its etiology, its intra and extra oral manifestations, as well as its signs and symptoms, in order to establish its differential diagnosis. To develop the review, a search was made for articles published between 2013 and 2023, which were in Portuguese or English, disregarding those that did not meet the selection criteria, in the end, 37 articles were used for its construction. It is concluded from the analysis of the articles that the diagnostic method is a consensus among the authors, through the correlation of clinical and histological characteristics, patient history and use of medications and, when necessary, a biopsy should be performed so that immunofluorescence can be performed. direct to distinguish diseases that have the same characteristics and tend to cause confusion in the diagnostic process. More in-depth studies on the subject are required.